ANALISIS KELAYAKAN FINANSIAL DAN STRATEGI PEMASARAN BUAH MELON DI GREEN HOUSE PONDOK PESANTREN NURUL FATTAH KABUPATEN TULANG BAWANG - Sholeha, Umi Lutfiyatus; Endaryanto, Teguh; Rufaidah, Erlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This research used two methods, namely descriptive methods and analytical methods. Sample used in this research was the Inthanon melon farming business by Nurul Fattah Islamic Boarding School in, Tulang Bawang District, Lampung. Financial feasibility of the Inthanon melon farming business was analyzed using five criteria, included NPV, Net B/C, IRR, and PP, while the prospects and marketing strategy of the melon farming business were analyzed using SWOT analysis. Results of the research show that the Inthanon melon farming by Pondok Pesantren Nurul Fattah is financially feasible to continue with an NPV calculation of IDR 738,604,504/500 m2, net B/C of 2.86, IRR of 27%, and PP for 6 years. Marketing strategies for melon fruit at Nurul Fattah Islamic Boarding School are to improve the quality of melons, and arrange a regular planting schedule for melons to avoid over supply of fruit on the market. In addition, another strategies are taking part in various bazaar activities, doing collaboration with melon processed food producers, maximizing the use of digital promotional media, sticking an attractive label on the fruit to make it look luxurious and known to people, increasing market share and strengthening the partnership network in particular with Superindo.  Keywords: feasibility analysis, melon, and marketing strategy